Socio-Philosophical Analysis Of Society’s Ideosphere - Sobirovich, Turdiev Bekhruz (Indonesian Journal Publisher, 2024)
Renewing the ideosphere of society is a complex and multifaceted process associated with changes in politics, economics, education, culture, and the social sphere. This process requires the active support and participation of all members of society, government bodies, educational and cultural institutions and other structures. This article, based on the philosophical context, analyzes the philosophical essence of the ideosphere of society, outlines the main elements that make up the ideosphere of society, the factors and reasons influencing its renewal.